PERHIASAN SEBAGAI PENANDA STRATIFIKASI MASYARAKAT PADA RELIEF LALITAVISTARA CANDI BOROBUDUR - , CHITRA PARAMAESTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Topic: Iconography study associated with the stratification of society depicted in the story of Lalitavistara on Borobudur reliefs. Issue: Is jewelry can be measured in a society stratified on Lalitavistara story? Objectives: To find out the variety of jewelry worn by the characters in Lalitavistara story and itâs relation to the society stratification. Methods: This research was conducted in description of the reliefs story and jewelry typology to determine the association between jewelry and society stratification. Conclusion: Society stratification system in Lalitiviatara story is closed stratification system which is the society has privilege in term of wearing jewelry. Related to the issue, Jewelry could be the indicator of stratification in society. Moreover, Lalitavistara reliefs also depicted the open stratification system, therefore the stratification of society beside refers to power and materials it also refers to human expertise to generated something. Key words: Jewelry, Iconography, Stratification, Society, Relief, Lalitavistara, Temple, Borobudur